Hemolysis in neonatal rats results in auditory impairment. (November 2014) - Li, Qi; Chen, Peipei; Guo, Weiwei; Fang, Ruping; Yang, Shiming
Abstract Conclusion: This study suggests that hyperbilirubinemia in the neonatal rat can impair auditory function and induce peripheral nerve pathology by reducing neurofilament-positive cells in spiral ganglion neurons (SGNs). This finding indicates a potential connection between hyperbilirubinemia and auditory impairment. Objective: To establish a neonatal rat hyperbilirubinemia induced by hemolysis and assess the possible link between hyperbilirubinemia and auditory impairment. Methods: Wistar rats were divided into two groups – a bilirubin exposure group injected with phenylhydrazine hydrochloride at 7 and 28 days of age to induce hyperbilirubinemia, and a control group given saline. Auditory brainstem response (ABR) and distortion product otoacoustic emissions (DPOAEs) were determined to assess auditory function. Cochlea basilar membrane stretch preparations and cochlear frozen sections were examined for morphological changes in hair cells and SGNs. Results: At day 7, ABR wave I, III, and V latencies, and I–III, I–V interwave intervals (IWIs) in the experimental group were significantly prolonged compared with those in the control group. ABR thresholds were also elevated in the experimental group. We found no significant difference in DPOAEs in the bilirubin exposure group compared to the control group. The ABRs and DPOAEs in the experimental group were restored at age 28 days. Cochlear hair cells showed no signs of loss in either group; however, the total number of neurofilament-positive cells in SGNs was significantly reduced in the phenylhydrazine-treated animals.